Health Capital Provision and Human Capital Accumulation - Leonid V. Azarnert (Center for Economic Studies and ifo Institute (CESifo), 2020)
This article analyzes the effect of public policy intervention in the production of health capital on fertility, private investment in children's health and education and human capital accumulation. I have used a growth model with endogenous fertility, in which the usual parental trade-off between the quantity and quality of their children is augmented with an additional factor that affects children's human capital, which is health. I analyze the overall society-wide effect of public policy intervention and derive a condition that determines precisely whether public provision of free health services increases or decreases the average level of human capital in the society.
Keywords: D30; I12; J10; J13; J24; O10; O40; 330; fertility; health capital; human capital; growth